2019
DOI: 10.1038/s41598-019-43115-8
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety assessment of two enterococci phages in an in vitro biofilm wound model

Abstract: Chronic wounds affect thousands of people worldwide, causing pain and discomfort to patients and represent significant economical burdens to health care systems. The treatment of chronic wounds is very difficult and complex, particularly when wounds are colonized by bacterial biofilms which are highly tolerant to antibiotics. Enterococcus faecium and Enterococcus faecalis are within the most frequent bacteria present in chronic wounds. Bacteriophages (phages) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 65 publications
3
52
0
1
Order By: Relevance
“…In this scenario, bacteriophages appear to be an alternative strategy to treat biofilm-forming infections. Over the past few years, numerous studies have been carried out investigating the effectiveness of phages against mono-and dualspecies biofilm (Sillankorva et al, 2010;Chhibber et al, 2015;Gutierrez et al, 2015;Gonzalez et al, 2017;Melo et al, 2019). Many of these studies pointed to a notable dependency between the phages and the bacterial species involved on the biofilm for the efficacy of the phage treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, bacteriophages appear to be an alternative strategy to treat biofilm-forming infections. Over the past few years, numerous studies have been carried out investigating the effectiveness of phages against mono-and dualspecies biofilm (Sillankorva et al, 2010;Chhibber et al, 2015;Gutierrez et al, 2015;Gonzalez et al, 2017;Melo et al, 2019). Many of these studies pointed to a notable dependency between the phages and the bacterial species involved on the biofilm for the efficacy of the phage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages (phages) have regained interest as promising therapeutic option in fighting biofilmrelated infections due to their rapid bactericidal activity, the self-amplification ability and potential biofilm degradative properties (Harper et al, 2014). However, there are only limited studies investigating the activity of phages against polymicrobial biofilms (Sillankorva et al, 2010;Kay et al, 2011;Chhibber et al, 2015;Oliveira et al, 2018;Melo et al, 2019) and just recently Akturk et al (2019) evaluated the simultaneous and staggered administration of a P. aeruginosa-targeting monophage and conventional antibiotics on S. aureus/P. aeruginosa dualspecies biofilms.…”
mentioning
confidence: 99%
“…Phages are being considered for the treatment of multidrug-resistant (MDR) bacterial infections, including enterococcal infections. Recent studies have demonstrated the potential for phagebased therapies against systemic and biofilm-associated enterococcal infections (18)(19)(20)(21)(22). The decolonization of intestinal MDR E. faecalis may be achieved through the action of phage predation which selects for cell wall variants that are rendered sensitive to antibiotic therapy (23).…”
mentioning
confidence: 99%
“…Los factores de virulencia del E. faecalis están relacionados a varios elementos de la Pedraza-Maquera KI bacteria, tales como: la proteína de superficie extracelular del Enterococcus (Esp), la cual promueve la adhesión, colonización y evasión del sistema inmune; la presencia de un pilli que es importante en la producción del biofilm, la cual se ubica en la proteína Bps; la citolisina (Cyl) o hemolisina, le da propiedades B-Hemolíticas en humanos y es bactericida ante otras bacterias Gram positivas; la gelatinasa, (GelE) provee nutrientes a la bacteria degradando el tejido del huésped e interviene de alguna forma en la formación de biofilm (20); la sal biliar hidrolasa, le permite hidrolizar la bilis, este factor en conjunto con la producción de capsula y la formación de biofilm contribuyen con la patogénesis de este organismo (15); la hialuronidasa despolimeriza a la molécula de mucopolisacárido del tejido conectivo que le permite a la bacteria diseminarse; las determinantes de feromonas (Eep) modulan la respuesta inflamatoria in vivo; el antígeno A (EfaA) se asocia con la adherencia de la bacteria a células vivas o superficies inertes como la dentina; la proteína de superficie celular (Ace) le permite unirse al colágeno y jugaría un rol importante en la endocarditis (20); la sustancia de agregación (Agg), actúa en la unión de la bacteria al epitelio intestinal, células del epitelio renal, neutrófilos humanos y macrófagos. Esto es corroborado en un estudio reciente realizado por Melo et al en el 2019, que refiere que las heridas crónicas son difíciles de tratar porque son colonizadas por biopelìculas bacterianas que son altamente tolerantes a los antibióticos (15,(21)(22)(23).…”
Section: Enterococcus Faecalisunclassified